Evolution of high‐mass X‐ray binaries in the small magellanic cloud. Issue 1 (28th March 2019) - Yang, J.; Wik, D. R.; Zezas, A.; Laycock, S. G. T.; Hong, J.; Xu, R.
Abstract : To understand the progenitor of rotation‐powered pulsars, we compare them with accreting High‐Mass X‐ray binary pulsars, (hereafter X‐ray pulsars), in the small magellanic cloud. The diagram of spin period vs. period derivative shows that isolated neutron stars could be evolved from X‐ray pulsars. The pulsars with long spin period might spin up to 0.001–1 s. The binary orbit is disrupted by a third body in the universe, and the binaries are detached. Therefore, some of the pulsars become isolated neutron stars.